Childhood systemic lupus erythematosus (CSLE) and its psychological impact: dual tertiary centre experience - Amiruddin, Mushamma Mursheeda (2023)
Introduction: This study investigated the potential psychological problems in children with systemic lupus erythematosus (SLE) compared to healthy children. Methods: A non-probability sample study was performed on children with SLE, and their peers aged 6 to 18 years. The Child Behaviour Checklist for Ages 6–18 (CBCL 6–18) was completed by the participant's parents. The questionnaire helps to assess the children's emotional and psychological issues. In addition, their demographic and clinical information was also gathered. The analysis of CBCL scores was performed using independent t-tests. Results: A total of 111 children were recruited, 41 of whom had SLE. Most of the SLE participants were Malay females aged 13–15 who are attending secondary school. Most of them are from low socioeconomic status. The findings revealed that the children with SLE scored substantially higher than the healthy children (the control group) on three CBCL subscales. The subscales mentioned are internalising subscale [mean difference of 3.13, 95% confidence interval (CI) [0.30, 5.95] and P = 0.03], withdrawn subscale [mean difference of 1.50, 95% CI [0.42, 2.60] and P = 0.01], and attention problem [mean difference of 2.14, 95% CI [0.35, 3.94] and P = 0.02]. Besides that, SLE participants' scores on other subscales, including anxiety and somatic, were also considerably higher than the control group, although these differences were not statistically significant. Conclusion: Children with SLE are perceived to have greater psychological problems compared to their healthy peers. They were more socially withdrawn and inattentive, as indicated by the CBCL scores.